FACTORS THAT AFFECT AUDIT DELAY IN COMPANIES MANUFACTURE WHICH REGISTERED IN EXCHANGE EFFECT INDONESIA YEAR 2018-2022 (Jurnal Ipteks Terapan, 2024)
The aim of this research is to prove the influence of company size, profitability, solvency, and company age in manufacturing companies listed on the Stock Exchange Effect Indonesia (IDX). In study This technique taking sample Which used with method purpose sampling. This research is a type of quantitative research using applications spss version 27. There are tests used consisting of the classic assumption test, namely the normality test, multicollinearity, heteroscedasticity, autocorrelation, test regression linear double, hypothesis (Test Q), hypothesis (Test F), coefficient (R2). Population Which used in study This company manufacture property and real estate sectors listed on the IDX starting from 2018-2022. Results of this research show that (1) Size Company No influential in a way significant to Auditing Delay. (2) Profitability has a significant influence on Audit Delay. (3) Solvency no has a significant effect on Audit Delay. (4) Company age has no influence significant to Auditing Delay. Results testing Test Assumption Classic Which through process test Normality, Multicollinearity Test, Autocorrelation Test, Heteredasticity Test, Linear Regression Analysis Multiple, Coefficient (R2), Hypothesis (F Test), Hypothesis (T Test). Adjusted R Square effect 4.3% to Auditing Delay and the rest 95.7% influenced other variables